More Curious Jane : science + design + engineering for inquisitive girls - Josse, Elissa; Robertson, Bethany (Sterling Children's Books, 2019)
Packed with fun hands-on projects introducing girls to even more science + design + engineering concepts. Whip up super-sticky and slimy putty, create a scratch-off card with a secret message, transform black canvas sneakers into out-of-this-world galaxies, make colorful soap in the shape of ice pops, and so much more!